Pengaruh covid-19 dan PMA terhadap PDRB Kabupaten/Kota di Provinsi Riau - Hannisa Sasilia Nasution; Ando Fahda Aulia; Darmayuda Darmayuda (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2023)
This research of study aims to analyze the effect of Covid-19 and Foreign Investment on the value of the Regency/City Gross Regional Domestic Product (GRDP) in Riau Province in 2017－2021. This study uses quantitative research methods with panel data analysis methods and processed using Eviews 10. The dependent variable used is Gross Regional Domestic Product in 11 Regency/Cities in Riau Province. The independent variables used in this research are the value of Foreign Investment and Covid-19 using dummy numbers. The results indicate that foreign investment has a positive but not significant effect on the GRDP of Regency/city in Riau Province. Meanwhile, the dummy variable of Covid-19 has a positive yet significant effect on Regency/City GRDP in Riau Province.